Export market experience, relational capital, and export performance in the context of different levels of psychic distance - Monika Sulimowska-Formowicz; Piotr Trąpczyński; Maja Szymura-Tyc (Entrepreneurial Business and Economics Review (EBER), 2024)
Objective: The objective of the article is to identify differences in the explanatory value of export market experience and relational capital as variables impacting export performance on markets characterised by high and low levels of psychic distance. We aimed to explore which of these resources turn out to be more useful in dealing with high and low levels of psychic distance between the exporter's home country and export markets. Research Design & Methods: The research is quantitative and based on primary data collected from exporting firms representing different manufacturing sectors, which have a track record of export market relationships using computer-assisted telephone interviews (CATI) in 2020. We ran ordinary least squares regression (OLS) analyses with IBM SPSS 23 software. Findings: The exporters' market-specific relational capital positively affects export performance, whereby this relationship is stronger for more distant markets. The impact of experience understood as tenure in the export market turned out to be insignificant for export performance. Implications & Recommendations: Exporters can leverage their relational capital to enhance export market performance instead of acquiring market-specific knowledge on their own. Since an overreliance on a foreign partner's resources may prevent the development of own capabilities, an approach relying on joint experiential learning seems more advisable. Our findings also suggest that tenure in an export market in itself does not guarantee superior performance, as the learning exposure in the foreign markets has to be given. Contribution & Value Added: We explore the relationships between a set of variables proposed by different theoretical views explaining export performance. The originality of our approach lies in the strategic optics we shed on firms' behaviour in high and low psychic distance markets. Depending on the contextual differences stemming from the level of psychic distance of markets firms strategise their presence in foreign markets deliberately relying on either their experience or market-specific relational capital.
Keywords: F23; L25; M16; 330; export market performance; export experience; relational capital; relationship quality; psychic distance